2022
DOI: 10.1261/rna.079391.122
|View full text |Cite
|
Sign up to set email alerts
|

The daunting task of modifying ribosomal RNA

Abstract: One of the most basic tasks of every cell is the synthesis of ribosomes, yet the process is so complex that we are only beginning to comprehend it. In human cells, the final product contains four RNAs and 79 proteins forming a large ribonucleoprotein, the ribosome. About twice as many factors are involved in assembly of these protein synthesizing machines. Additionally, some 200 small nucleolar ribonucleoproteins (snoRNPs) function in the modification of pre-ribosomal RNA (pre-rRNA) at a similar number of ribo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“… 23 As nascent rRNA is transcribed, enzymes such as fibrillarin (FBL, part of the C/D Box snoRNP complex) localize to the DFC to promote initial rRNA modification and cleavage steps. 24 , 25 Finally, the GC contains various proteins that assist in further rRNA processing and binding to ribosomal proteins (r-proteins), ultimately forming nearly complete RSUs, which then move into the nucleoplasm and the cytoplasm. 22 , 26 , 27 The size of the compartments suggests that rRNA processing and folding in the GC are the ratelimiting steps for RSU assembly.…”
Section: Introductionmentioning
confidence: 99%
“… 23 As nascent rRNA is transcribed, enzymes such as fibrillarin (FBL, part of the C/D Box snoRNP complex) localize to the DFC to promote initial rRNA modification and cleavage steps. 24 , 25 Finally, the GC contains various proteins that assist in further rRNA processing and binding to ribosomal proteins (r-proteins), ultimately forming nearly complete RSUs, which then move into the nucleoplasm and the cytoplasm. 22 , 26 , 27 The size of the compartments suggests that rRNA processing and folding in the GC are the ratelimiting steps for RSU assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the modification data and annotated snoRNAs of 25S, 5.8S, and 18S obtained from snOPY, we observed that SnoR12–1b snoRNA guides the most modifications in 25S rRNA, primarily associated with methylation rather than pseudouridylation. On the other hand, it is also important to note that there is a lack of information modification sites of rRNA in public repositories [ 27 , 16 , 28 ]. However, ongoing efforts are underway to identify modifications across all existing rRNA types.…”
Section: Methods Validationmentioning
confidence: 99%
“…For example, nascent pre-rRNA molecules undergo, after transcription, a series of processing steps to produce the mature rRNA molecule. Prior to cleavage by exoand endonucleases, the pre-rRNA molecule undergoes a series of nucleoside modifications by methylations and pseudouridylations that is guided by snoRNAs [57]. snoRNAs may serve as miRNAs precursors, e.g., snoRNA called ACA45 can be processed into a mature miRNA of 21 nt length by the RNAse III endoribonuclease dicer.…”
Section: Small Nucleolar Rnasmentioning
confidence: 99%